Application of Discharge Planning on the Patient with Postoperative Cystectomy e.c. Urether Carcinoma: Case Study - Herlina Puspita; Yulia Kurniawati; Dicky Endrian Kurniawan; Maman Suparman (KHD Production, 2024)
Urethral carcinoma or urethral cancer is that is located in the urethra is one of the rarest types of urological cancer. Cystectomy is a surgical procedure to remove the bladder. The condition of post operative patients is of particular concern to health workers. Most patients and families do not know about post-operative patients care while at home. Therefore, the knowledge and attitudes of patients and families regarding post-operative care are important things that need to be educated by health workers. Providing education to patients and families before returning home is called discharge planning. Based on data from October 9 to October 31, there were patients diagnosed with urethral carcinoma who were treated in the Parangtritis room at Dr. Hospital Saiful Anwar Malang. This research method uses descriptive research with a case study design. Implementation of discharge planning starts from the time the patients first come to the room until the day the patients return home. The implementation of discharge planning for patients went well. Nurses can carry out their duties as health workers in carrying out discharge planning procedures.